Reflection on Educators' "Penyakit" to Improve Professional Competence in the Perspective of Islamic Religious Education - Amrizon, Amrizon; Ritonga, Mahyudin (Ruhama : Islamic Education Journal, 2024)
The teaching profession is central to the continuity of education, but not all educators realise this important position, so there are still some teachers who have a "Penyakit" and need a way to overcome it. Therefore, this research was conducted to find an effective remedy to overcome the teacher's "Penyakit" by looking at the perspective of Islamic education. The research was conducted with a qualitative approach, the main source of research is library references obtained from various books, journals and relevant scientific works, data collected from existing sources with careful reading techniques, then taking the meaning contained in the source. The results of the analysis prove the importance of optimising the central position of the teacher in the learning process. The position of the teacher in the classroom determines the success of learning, so the teaching profession is always fostered and developed, popularly known as "never ending development". Development is carried out by recognising the characteristics of the teaching profession first and at the same time providing feedback to the teaching profession. Islamic education views that the main key for someone who chooses to work as a teacher is sincerity, perseverance, istiqamah and responsibility.